Negative Impact of Sadness on Response Inhibition in Females: An Explicit Emotional Stop Signal Task fMRI Study - Ding, Jianrui; Wang, Yongming; Wang, Chuan; d’Oleire Uquillas, Federico; He, Qinghua; Cheng, Li; Zou, Zhiling (Frontiers in Behavioral Neuroscience, 2020)
Response inhibition is a critical cognitive ability underlying executive control over reactions to external cues, or inner requirements. Previous studies suggest that high arousal negative emotions (e.g., anger or fear) could impair response inhibition in implicit emotional stop signal tasks. However, studies exploring how low arousal negative emotions (e.g., sadness) influence response inhibition remain sparse. In the current study, twenty female college students performed an explicit emotional stop signal task to explore the influence of sadness on response inhibition and its neural mechanism. Participants are instructed to press a button to sad or neutral facial stimuli while inhibiting their response during the presentation of a stop signal. Results showed that sad stimuli were related to increased stop signal reaction time (SSRT) (i.e., worse response inhibition). Compared with neutral condition, higher activation during sad conditions was found within the right superior frontal gyrus, right insula, right middle cingulate cortex, bilateral superior temporal gyrus, left lingual gyrus and right motor cortex. These findings indicated that sadness, like other negative emotion, may impair response inhibition in an explicit way and highlight the explicit emotional stop signal task as a new paradigm to investigate the subtle interaction between negative emotion processing and cognitive control.